2017
DOI: 10.1007/978-1-4939-7156-5_27
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Assessment of Abiotic Stress in Date Palm: Salinity and Drought

Abstract: Date palm is one of the major crops growing in regions where abiotic stress conditions are extreme. Abiotic stress affects plant growth, development, physiology, and biochemical processes. This chapter describes a protocol to evaluate the response of date palm cultures to abiotic stresses. Tolerance to salinity stress is assessed using calcium chloride (CaCl), potassium chloride (KCl), and sodium chloride (NaCl) at 11.96, 12.06, and 9.45 g/L, respectively (equivalent to 0.8 MPa osmotic potential), with differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Abiotic stresses, such as drought, high salt, darkness, low temperature, phytohormone, are common environmental factors in nature that severely restrict the growth and development of crops [8] . Currently, the annual yield loss of major crops due to abiotic stress is over 50% on average worldwide [9]. Studies have demonstrated that abiotic stress can dehydrate cells, destroy the cell membrane system, affect the enzyme activity on the cell membrane, and disrupt metabolism [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Abiotic stresses, such as drought, high salt, darkness, low temperature, phytohormone, are common environmental factors in nature that severely restrict the growth and development of crops [8] . Currently, the annual yield loss of major crops due to abiotic stress is over 50% on average worldwide [9]. Studies have demonstrated that abiotic stress can dehydrate cells, destroy the cell membrane system, affect the enzyme activity on the cell membrane, and disrupt metabolism [10,11].…”
Section: Introductionmentioning
confidence: 99%